2007
DOI: 10.1111/j.1399-6576.2007.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse pressure variation as a tool to detect hypovolaemia during pneumoperitoneum

Abstract: Background:  Pulse pressure variation (ΔPP) and systolic pressure variation (SPV) induced by mechanical ventilation have been proposed to detect hypovolaemia and guide fluid therapy. During laparoscopic surgery, chest compliance is decreased by pneumoperitoneum. This may affect the value of SPV and ΔPP as indicators of intravascular volume status. Thereby, we investigated the effects of pneumoperitoneum and hypovolaemia on SPV and ΔPP.Methods:  We measured ΔPP, SPV and the inspiratory (Δup) and expiratory (Δdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
5
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 32 publications
2
26
5
5
Order By: Relevance
“…This reported lack of increase in SVV is questionable because in all reported animal studies (12)(13)(14)(15), SVV increased after elevation of intra-abdominal pressure and/or pneumoperitoneum. We recently found that pneumoperitoneum increased SVV in humans (6), and furthermore, many animal studies showed that other dynamic indices such as systolic pressure variation and pulse pressure variation (23,24) also increased during intra-abdominal hypertension (12)(13)(14)(15)(25)(26)(27) Our results relating to PVI and SVV after pneumoperitoneum were different than those of Høiseth et al (11) and Liu et al (3), and the reason for the discrepancy is unclear. However, we suppose this relates to differences in study design.…”
Section: Discussioncontrasting
confidence: 56%
“…This reported lack of increase in SVV is questionable because in all reported animal studies (12)(13)(14)(15), SVV increased after elevation of intra-abdominal pressure and/or pneumoperitoneum. We recently found that pneumoperitoneum increased SVV in humans (6), and furthermore, many animal studies showed that other dynamic indices such as systolic pressure variation and pulse pressure variation (23,24) also increased during intra-abdominal hypertension (12)(13)(14)(15)(25)(26)(27) Our results relating to PVI and SVV after pneumoperitoneum were different than those of Høiseth et al (11) and Liu et al (3), and the reason for the discrepancy is unclear. However, we suppose this relates to differences in study design.…”
Section: Discussioncontrasting
confidence: 56%
“…Appropriate fluid therapy is of the utmost importance for optimizing cardiac performance and organ perfusion during IAH (15). It has been shown that cardiac filling pressures, such as CVP and pulmonary artery occlusion pressure, in the presence of elevated IAP may be falsely increased, hence misleading adequate fluid therapy (16). Recently, it has been demonstrated that elevated IAP increases the static variables of preload such as PPV and systolic pressure variation (SPV), especially in cases of hypovolemia (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Fluid responsiveness in IAH is defined as a PPV above 20% rather than the usual 12% threshold. Systolic pressure variation should not be used in the setting of increased IAP or ITP because the increase seen in IAH and ACS only reflects a ΔUp phenomenon [67,68]. 8.…”
Section: Copp = Dbp -Paop = Dbp -Itpmentioning
confidence: 99%